Role of Low-Molecular-Mass Penicillin-Binding Proteins, NagZ and AmpR in AmpC β-lactamase Regulation of Yersinia enterocolitica - Liu, Chang; Li, Chuchu; Chen, Yuhuang; Hao, Huijing; Liang, Junrong; Duan, Ran; Guo, Zhaoke; Zhang, Jing; Zhao, Zhongzhi; Jing, Huaiqi; Wang, Xin; Shao, Shihe (Frontiers in Cellular and Infection Microbiology, 2017)
Yersinia enterocolitica encodes a chromosomal AmpC β-lactamase under the regulation of the classical ampR-ampC system. To obtain a further understanding to the role of low-molecular-mass penicillin-binding proteins (LMM PBPs) including PBP4, PBP5, PBP6 and PBP7, as well as NagZ and AmpR in ampC regulation of Y. enterocolitica, series of single/multiple mutant strains were systematically constructed and the ampC expression levels were determined by luxCDABE reporter system, reverse transcription-PCR (RT-PCR) and β-lactamase activity test. Sequential deletion of PBP5 and other LMM PBPs result in a continuously growing of ampC expression level, the β-lactamse activity of quadruple deletion strain YEΔ4Δ5Δ6Δ7 (pbp4, pbp5, pbp6 and pbp7 inactivated) is approached to the YEΔD123 (ampD1, ampD2 and ampD3 inactivated). Deletion of nagZ gene caused two completely different results in YEΔD123 and YEΔ4Δ5Δ6Δ7, NagZ is indispensable for YEΔ4Δ5Δ6Δ7 ampC derepression phenotype but dispensable for YEΔD123. AmpR is essential for ampC hyperproduction in these two types of strains, inactivation of AmpR notable reduced the ampC expression level in both YEΔD123 and YEΔ4Δ5Δ6Δ7.